POTENSI BAKTERI ENDOFIT AKAR UBI JALAR (IPOMOEA BATATAS L.) ASAL KABUPATEN SORONG PAPUA BARAT SEBAGAI AGENSIA BIOKONTROL MELOIDOGYNE SPP. - ., Tuminem; Sinaga, Meity S; ., Giyanto (Universitas Lampung, 2015)
Potency of sweetpotato (Ipomoea batatas L.) root endophytic bacteria from Sorong District West Papua as biocontrol agent of Meloidogyne spp. Root knot nematodes/RKN, Meloidogyne spp. is one of the important pathogens in sweet potato plant. The disease incidence rate by the RKN on sweetpotato crop in Sorong District reached 88.77%. This study aims to get the sweet potato root endophytic bacteria that have potential as biocontrol agents against Meloidogyne spp. Endophytic bacteria was isolated from the roots of healthy sweet potato sampled from Sorong District, West Papua Province. Isolation and selection of bacteria using TSA media. Selected bacterial isolates, which were non-pathogenic to plants and humans then were identified with PCR technique using universal primer 63-F / 1387-R. The ability of bacteria to produce the lipase enzyme was selected using the media NB agar and rhodamine B. The protease enzyme-producing bacteria were selected using skim milk media. The chitinase enzyme-producing bacteria were selected using the colloidal chitin media. Production of cyanide was detected using filter paper soaked in a solution of CDS. The effectiveness of culture filtrate of bacteria as biocontrol agents was measured based on the percentage of 2nd juvenile mortality and egg hatching of Meloidogyne spp. Four isolates of endophytic bacteria, that were Enterobacter sp EAS (1a), Enterobacter sp. EAS (3a) Enterobacter ludwigii EAS (4), and Burkholderia cepacia EAS (6) produced lipase and protease. In addition, B. cepacia EAS (6) also produced chitinase. Those isolates caused mortality of the 2nd juvenile 81.4 to 95.2% and inhibited the egg hatching of Meloidogyne spp. 53.13 to 81.92%.